Self-Repair Strategies in English Conversations to Teach English Interaction Skill - Adi Irma Suryadi; Latifah Fatmawati (Universitas Islam Negeri (UIN) Mataram, 2020)
The demand for language education is developed along with technological advancements. English teachers have to improve students' interaction skills, especially conversation. This paper aimed to make suggestions about how to implement repair strategies in teaching English spoken interaction skills to EFL learners in Indonesia based on CEFR. The materials are taken from English conversations in an American television sitcom. The characters' utterances were analyzed qualitatively, and the occurrences analyzed quantitatively. The result shows there are six kinds of self-initiated self-repair, and the most frequently used is repetition, then hesitation pauses, and followed by searching a word. Moreover, this paper provided some suggestions for applying self-initiated self-repair strategies for teaching English spoken interaction skills.